OIL CONTENT IN SEDIMENT AND ITS RELATION WITH ABUNDANCE MACROZOOBENTHOS IN THE TELUK NIBUNG TANJUNG BALAI ASAHAN NORTH SUMATRA - Andika Sitohang; Syahril Nedi; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in November 2015. This study about Oil Content in Sediment and its Relation with Abundance Macrozoobenthos in the Teluk Nibung Tanjung Balai Asahan North Sumatra. The methodology that was used to research this is a method of survey, and divided into 3 station and in 1 station there are 3 points of sampling. Samples have been taken later incorporated to plastic and given sample macrozoobenthos solution formalin 10 % then taken and in Laboratorium analysis.The results of the analysis oil content in the Teluk Nibung during the survey obtained that oil content sediment station highest on 1 ( 600 ppm ) and oil content the lowest in 2 station (333,33 ppm ). Then the analysis identification Macrozoobenthos in may at these waters are 10 different species in this study there are several species dominating the Mitrela ligulla and N.Echinatus. The abundance of these species because the species is still can tolerate environmental stress at the base of the Teluk Nibung .Based on the linear regression simple , obtained the oil content with abundance of Makrozoobenthos strong correlation and have negative value that means the higher oil content and abundance Makrozoobenthos the lower.Keywords: minyak pada sedimen, makrozoobenthos